2020
DOI: 10.1002/ags3.12363
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repeat liver resection

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Besides, the proper trocar placement should be adjusted according to operation custom of the surgeon, as well as the changed liver anatomy and formed adhesions caused by previous hepatectomy. Moreover, for the consideration of future abdominal operations, it is better to avoid unnecessary extensive adhesiolysis when the adhesion does not affect the operative procedure ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the proper trocar placement should be adjusted according to operation custom of the surgeon, as well as the changed liver anatomy and formed adhesions caused by previous hepatectomy. Moreover, for the consideration of future abdominal operations, it is better to avoid unnecessary extensive adhesiolysis when the adhesion does not affect the operative procedure ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The location of trocar hole should be adjusted according to the newest liver anatomy and the adhesions formed after the previous surgery. Unnecessary adhesiolysis should also be avoided for favoring the future abdominal surgeries (35,36). As for postoperative survival, our results revealed that patients receiving LRH had a significantly better OS than patients receiving ORH (P < 0.05).…”
Section: Discussionmentioning
confidence: 71%
“…Laparoscopy can be used to distinguish adhesions from organs with a clear surgical field of view, and the tension created by a pneumoperitoneum may facilitate closer adhesiotomy, allowing for meticulous maneuvering to reduce serious complications, including massive bleeding and intestinal damage 1,6,16–19 . Additionally, laparoscopy eliminates the need for extensive adhesiolysis, 20,21 which is possibly the reason for the shorter operative time and lesser intraoperative bleeding volume in LRLR than in ORLR in this study. LRLR reduces the occurrence of ascites, 17,19 which might be explained by the fact that the abdominal wall’s collateral circulation and the diaphragm’s lymphatic flow in patients with portal hypertension are minimally disrupted in laparoscopic surgery than in open surgery; in LRLR, only four or five trocars are required in the upper quadrant of the abdomen instead of a large subcostal incision 18 .…”
Section: Discussionmentioning
confidence: 83%